2022
DOI: 10.33751/ekologia.v22i1.4739
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Ekstrak Codium, Halimeda, Dictyota, Chondrus, Glacillaria Sebagai Sumber Pigmen Dan Antioksidan Alami

Abstract: Macroalgae is one of the marine biological resources that has an important role in terms of economy, as a source of food and medicine that is beneficial to health. This study aims to determine the source of natural pigments and antioxidants extracts of algae Codium, Halimeda, Dictyota, Chondrus, and Glacillaria using acetone, Folin Ciocalteu, and 1,1-Diphenyl-2-Picrylhydrazil (DPPH) reagents. The method includes sampling, measuring water content by gravimetry, making extracts using maceration method, qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results showed that the IC 50 value of H. tuna methanolic extract was 299.98 ± 121.15 ppm, whereas, for BHT, it was 98.82 ± 21.60 ppm, and for vitamin C, it was 20.48 ± 1.64 ppm. Haryani et al (2022), reporting the IC 50 of 3.57 ppm. Meanwhile, BHT has a lower IC 50 value than the one reported in a study by Mandrekar et al (2019), which was 83.30 ppm.…”
Section: Dpph (22-diphenyl-1-picrylhydrazyl) Assaymentioning
confidence: 99%
“…The results showed that the IC 50 value of H. tuna methanolic extract was 299.98 ± 121.15 ppm, whereas, for BHT, it was 98.82 ± 21.60 ppm, and for vitamin C, it was 20.48 ± 1.64 ppm. Haryani et al (2022), reporting the IC 50 of 3.57 ppm. Meanwhile, BHT has a lower IC 50 value than the one reported in a study by Mandrekar et al (2019), which was 83.30 ppm.…”
Section: Dpph (22-diphenyl-1-picrylhydrazyl) Assaymentioning
confidence: 99%